2006
DOI: 10.1002/jhet.5570430126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel halogenated cryptolepine analogues

Abstract: Cryptolepine (5-N-methyl-10-H-indolo [3,2-b]quinoline) is an indoloquinoline alkaloid present in the roots of Cryptolepis Sanguinolenta. In its hydrochloride form the alkaloid presents a number of bioactivities. The alkaloid also has cytotoxic properties that are likely to be due to its abilities to intercalate into DNA and inhibit the enzyme topoisomerase II, as well as the synthesis of DNA. In this research project five novel analogues of cryptolepine were chosen for synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Of those synthesized, 7,11-dichlorocryptolepine (2) showed the highest cytotoxic activity against MAC15a (colon adenocarcinoma) cells with an IC 50 value of 14.4 ± 2.8 μM (after 1 hour exposure). 7,8 Whilst the literature is generally in agreement that cryptolepines are an interesting target for anti-cancer research, the mode of action is still not that well understood. 9 For example, it is observed that the cytotoxicity of cryptolepine is linked to its ability to inhibit the topoisomerase II enzyme so it would be expected that bromo and iodo compounds would show greater topoisomerase II inhibition owing to their increased lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Of those synthesized, 7,11-dichlorocryptolepine (2) showed the highest cytotoxic activity against MAC15a (colon adenocarcinoma) cells with an IC 50 value of 14.4 ± 2.8 μM (after 1 hour exposure). 7,8 Whilst the literature is generally in agreement that cryptolepines are an interesting target for anti-cancer research, the mode of action is still not that well understood. 9 For example, it is observed that the cytotoxicity of cryptolepine is linked to its ability to inhibit the topoisomerase II enzyme so it would be expected that bromo and iodo compounds would show greater topoisomerase II inhibition owing to their increased lipophilicity.…”
Section: Introductionmentioning
confidence: 99%